Utilização da reação em cadeia da polimerase (PCR) para detecção de leite bovino em leite caprino - Rodrigues, Noádia Priscila Araújo (2011)
The goat milk provides nutrients essential for the proper operation of human organism has gained importance in consumer market. There is an urgent need for studies that provide tools for detection of adulteration in goat milk by addition of bovine milk, a practice that has become a recidivist. This study aimed to provide a tool for validation in Brazilian species of goat milk and cow milk technique of polymerase chain reaction, which had a detection threshold of 0,5%. And used the method of phenol-chloroform and a commercial kit for the extraction of DNA of high quality and purity. The technique was used in conjunction milk samples collected from processing plants of goat milk in western cariri paraibano and found the presence of bovine milk in 37,5% of samples.